(untitled) (Revista Sistemas de Producción Agroecológicos, 2016)
The program of hazard analysis and critical control points (HACCP), is a systematic process that applies to ensure the safety and quality of food, and at the same time, functions as a security system that relies on risk prevention by analyzing the production process, defining potential hazards and establishing critical control points to keep them from reaching the customer unsafe food. The rule ISO 22000 is a certifiable international standard which specifies the requirements for a Food Safety System, by incorporating all the elements of Good Manufacturing Practice (GMP) and HACCP, together with a proper management system, which allows the organization demonstrate that the products it supplies meet the demands of its customers, as well as regulations that are applied to food security. ISO rule and HACCP have a formalized approach to ensure the quality of food helping companies to demonstrate their commitment to meeting the demands of legislation and customers; the implementation of this regulation in a plant of benefit animal located in Villavicencio, Colombia, which offers its end products taking into account: the physicochemical properties of meat, maturation processes, care to prevent the risk of contamination with various substances to which the channel is exposed during preparation: mechanical grease, hair, bone marrow, skin, feces, rumen contents, saw splinters, sand, abscesses, residues of drugs or vaccines. Full identification and correction of observed contaminations helps to ensure the quality of the product delivered to the consumer, so it is important that be preserved the image and trust of the product to meet local market requirements, with a meat of excellent quality, presentation and safety that reaches the final consumer. Optimal identification of factors that alter the process, allows to implement corrective measures, which when applied promptly increase the efficiency of the process, whereby is improved the activities of operators reducing their days with adequate rest intervals, also achieve agility in deliveries of channels, turn to other areas of the plant and butchering, washing of viscera and other, have the raw material for processing.